Short-Term Stability of Serum and Liver Extracts for Untargeted Metabolomics and Lipidomics - Hricko, Jiri; Rudl Kulhava, Lucie; Paucova, Michaela; Novakova, Michaela; Kuda, Ondrej; Fiehn, Oliver; Cajka, Tomas (Antioxidants (Basel, Switzerland), 2023)
Thermal reactions can significantly alter the metabolomic and lipidomic content of biofluids and tissues during storage. In this study, we investigated the stability of polar metabolites and complex lipids in dry human serum and mouse liver extracts over a three-day period under various temperature conditions. Specifically, we tested temperatures of -80 °C (freezer), -24 °C (freezer), -0.5 °C (polystyrene box with gel-based ice packs), +5 °C (refrigerator), +23 °C (laboratory, room temperature), and +30 °C (thermostat) to simulate the time between sample extraction and analysis, shipping dry extracts to different labs as an alternative to dry ice, and document the impact of higher temperatures on sample integrity. The extracts were analyzed using five fast liquid chromatography-mass spectrometry (LC-MS) methods to screen polar metabolites and complex lipids, and over 600 metabolites were annotated in serum and liver extracts. We found that storing dry extracts at -24 °C and partially at -0.5 °C provided comparable results to -80 °C (reference condition). However, increasing the storage temperatures led to significant changes in oxidized triacylglycerols, phospholipids, and fatty acids within three days. Polar metabolites were mainly affected at storage temperatures of +23 °C and +30 °C.
Keywords: shipping; lipidomics; liver; oxidation; stability; mass spectrometry; liquid chromatography; tissue; metabolomics; LC-MS; serum